Impact of inflation in the consumption of poor households in the Philippines - Fernandez, Allison Bluette Diwa; Salgado, Dana Mae Dadal; Reside, Renato Jr. E. (Quezon City School of Economics, University of the Philippines Diliman, 2018)
Within the past years, there has been concerning increases in inflation rate in the Philippines. These increases pose impacts on different macroeconomic sectors such as agricultural, financial, economic etc. Thus, the research focuses on the impacts of the changes in inflation rate to the populace, which are the basic unit of a nation. Poverty, as one of the major problems the Philippines is facing throughout the years, has been the focus of the government by making several projects such as the conditional cash transfer, also known as Pantawid Pamilyang Pilipino Program (4Ps) and KALAHI Comprehensive and Integrated Delivery of Social Services Project to empower poor communities and provide monetary assistance. With these, the study aims to discuss the effect of inflation in the lower income households by measuring the changes in consumer spending and observing the trends of consumption of poor households during high and low inflation rate through various statistical methods.
Thesis (B.S. Economics) -- University of the Philippines Diliman
Keywords: Cost and standard of living -- Philippines; Poor -- Philippines; Inflation (Finance) -- Philippines